Triterpenoid Pentacyclic Antimalarial Activity from the Leaves of Erythrina variegata - Tati Herlina; Unang Supratman; Anas Urbanas; Supriyatna Sutardjo; Noor Rain Abdullah; Hideo Hayashi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2011)
In the course of our continuing research for novel antimalarial agent from Indonesian plants, the methanol extract of the Erythrina variegata leaves showed significant antimalarial activity against Plasmodium falciparum strain K1 in vitro with IC50 6.8 μg/mL. The methanol extract was separated by using variety of chromatography techniques. The chemical structure of an antimalarial compound was determined on the basis of spectroscopic evidence and compared to previous data then this compound is identified as a pentacyclic triterpenoid oleane derivative, namely 3,22,23-trihydroxy-oleane-12-ene. The pentacyclic triterpenoid, 3,22,23-trihydroxy-oleane- 12-ene showed antimalarial activity against 3D7 and K1 strains with IC50 4.3 μg/mL and 24 μg/mL, respectively. These results strongly suggested that E. variegata is a promising sources of antimalarial agents.